2006
DOI: 10.1118/1.2179151
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐composition imaging using coherent‐scatter computed tomography: Assessing bone health beyond bone mineral density

Abstract: Quantitative analysis of bone composition is necessary for the accurate diagnosis and monitoring of metabolic bone diseases. Accurate assessment of the bone mineralization state is the first requirement for a comprehensive analysis. In diagnostic imaging, x-ray coherent scatter depends upon the molecular structure of tissues. Coherent-scatter computed tomography (CSCT) exploits this feature to identify tissue types in composite biological specimens. We have used CSCT to map the distributions of tissues relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 47 publications
2
44
0
1
Order By: Relevance
“…Therefore, we relied on a density value of 1.3 mg/ cm 3 , which was reported for hard tissue. 27 Thus, the low percentage of tissue volume accounted for in our measurements could be due to a wrong estimate of collagen density in breast tissue, and this is the reason why data on tissue composition are presented in Table 1 as absolute values ͑in milligram per cubic centimeter͒ rather than as percentage composition. However, it could also indicate that an appreciable percentage of tissue volume is represented by constituents that do not absorb significantly in the red and near-IR spectral range.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, we relied on a density value of 1.3 mg/ cm 3 , which was reported for hard tissue. 27 Thus, the low percentage of tissue volume accounted for in our measurements could be due to a wrong estimate of collagen density in breast tissue, and this is the reason why data on tissue composition are presented in Table 1 as absolute values ͑in milligram per cubic centimeter͒ rather than as percentage composition. However, it could also indicate that an appreciable percentage of tissue volume is represented by constituents that do not absorb significantly in the red and near-IR spectral range.…”
Section: Resultsmentioning
confidence: 96%
“…In medical applications, several studies [23][24][25][26] have shown that there exist significant differences in the scatter signatures from cancerous and healthy tissue, for example in the blood [2], bone [27] and breast [28]. In addition, studies have shown that scatter imaging can be used to spatially resolve different materials using tomography [29,30] or coded apertures [31].…”
Section: Potential Applications Of X-ray Scatter Imagingmentioning
confidence: 98%
“…Other potential uses of spectral CT in biomedical imaging include: improved detection of microcalcifications in breast cancer [23,24]; imaging of high Z nanoparticles [22,25,26] potentially bridging the gap between CT and molecular imaging; quantification of materials in tissues such as fat or iron in the liver in the metabolic syndrome [27]; and in vivo imaging of tissue scaffolds [28,29].…”
Section: The Uses Of Spectral Informationmentioning
confidence: 99%